A Study of the Impact of Training and Management Development Program on the Various Aspects of Telecom Sector Employees in India (International Journal of Innovative Research in Engineering & Management, 2022)
Role of training and management  development programs have been discussed by several  authors. The contemporary world has so many changes in  businesses. It would be meaningful to study the impact of  training and MDP on employees. So, researchers have  selected the employees of telecom sector. The study is based  on a survey of 500 employees of BSNL and Airtel in the  Delhi NCR region. The research questionnaire consisted 30  items. The key factors explored were Training and MDP, Job  satisfaction, Employees’ performances, and employees’ self efficacy. The research suggested that training and MDP has  significant positive impact on employees.
Keywords: Telecom Industry; training and management development; Employee performance; job satisfaction and self-efficacy